A longitudinal analysis of the effectiveness of California's ban on cellphone use while driving. (June 2019) - Liu, Chenhui; Lu, Chaoru; Wang, Shefang; Sharma, Anuj; Shaw, John
Abstract: Cellphone use while driving is an increasingly serious threat for traffic safety and is prohibited in many jurisdictions. In California, the use of handheld cellphones while driving has been prohibited since July 1, 2008. Using interrupted time series analysis, this study explores the effectiveness of the ban by specifically analyzing the crashes caused by cellphone usage in California from 2002 to 2014. These crashes were thought to be able to reflect the role of the ban more accurately than total crashes. The ban was found effective in reducing the cellphone usage-caused crashes in terms of both crash frequency and crash proportion. The study also confirms that crashes caused by cellphone use produce more severe outcomes than other crashes. These findings show that the ban on handheld cellphone use while driving plays an important role for improving traffic safety in California. In addition, it is found that the ban motivates drivers to switch from handheld cellphones to hands-free cellphones, but in terms of crash severity, hands-free cellphone usage and handheld cellphone usage do not show significant differences. These findings support a complete ban on cellphone use while driving–not just a prohibition of handheld cellphone use. The study results are expected to provide new insights for future policy-making related to cellphone use while driving.